PDSA Cycles Show Improvements in Key Indicators in Deceased Donation: The Spanish Experience. (July 2018) - Manceau, Christel Terron; Ramos, Bibiana; Pont, Teresa; Masnou, Nuria; Rodriguez-Villar, Camino; Zambudio, Julio Domingo; Elizalde, Jose; Vallejo, Jorge; Rodriguez, Sergio; Diaz, Jose Maria; Bodi, Maria Amparo; Marazuela, Rosario; et al.
Abstract : ACCORD-Spain study group. Background: The objective of ACCORD-Spain is to promote cooperation between Donor Coordinators (DC) critical care professionals in the deceased donation process. Its specific objectives are: i) To describe the deceased donation pathway from patients dead as a result of a devastating brain injury (possible donors) ii) To identify opportunities for improvement in the said process implement small interventions for change using the Plan, Do, Study, Act (PDSA) methodology. We present the impact of these interventions at a national level. Patients and Methods: The project was developed in three phases: 1. Data were collected on the deceased donation pathway from possible donors aged 1 month-85 years in participating hospitals during 11/1/2014-4/30/2015. 2. After a dedicated training in the PDSA methodology, each center was asked to set up a working group in their hospital to analyze the local improvement opportunities and design (Plan), implement (Do) and evaluate the impact (Study) of a small intervention, to then incorporate it into their usual practice (Act). 3. To assess the impact of these interventions, data were collected on possible deceased donors in these hospitals during 11/01/15-04/30/16. We describe the deceased donation pathway before and after the 46 PDSA cycles designed and implemented by 43 hospitals participating in the three phases of the Project. Results: 37 interventions focused on the identification of possible donors outside of the intensive care unit (ICU): prospective follow-up of cases identified through the systematic review of neuroimages and/or diagnoses at hospital admission, development of notification criteria, design of posters and methods for early referral, preparation of protocols on intensive care to enable organ donation, verification of compliance with the systematic referral policy, training and continuous feed-back to professionals involved. Seven hospitals focused on the initiation or consolidation of a controlled Donation after Circulatory Death program and 2 in improvements in the family approach to discuss donation opportunities. Results pre and post-intervention are represented in table 1. Conclusions: The project reveals the existence of opportunities for improvement in the deceased donation process in our country, both in the identification of possible donors outside the ICU and in donation after circulatory death. Both areas must be subject to continuous evaluation. The PDSA methodology can facilitate the search for excellence and continuous improvement in organ donation.